Польське термінознавство: основні напрями дослідження - Казимирова, І.А. (Мовознавство, 2016)
У статті проаналізовано особливості розвитку польського термінознавства від найдавніших часів до наших днів; виокремлено основні парадигмальні, крос-парадигмальні та крос-аспектуальні напрями й аспекти термінознавчих пошуків. The article deals with the main research directions in Polish terminology. Author shows specific features of the terminology since the beginning till our days. There are the following main research areas in polish terminology at the end of XX-XXI century: scientific works of system-structural paradigm, which is presented by theoretical and methodological research, onomasiological, onomasemasiological and semasiological; cross-paradigmatic structural and functional studies; functional paradigms that studies predominant orientation of scientific research and focused on languages for special purposes, theoretical and applied, didactic, lexicographical, dialectological aspects of the terms; few works of cognitive research paradigm and cross-disciplinary research.